Financial Benefits from JIT Adoption: Effects of Customer Concentration and Cost Structure. - Balakrishnan, Ramji; Linsmeier, Thomas J. (The Accounting Review, 1996)
Examines whether firms exhibiting improved inventory utilization subsequent to just-in-time (JIT) adoption achieve a corresponding increase in their Return on Assets (ROA). Effects of JIT adoption; Effects of customer concentration; Effects of cost structure.